Daily Conversations on the Application “Hallo”: A New Approach to Assign Speaking Homework to Students - Le Thi, Huong; Nguyet, Dang Thi (International Journal of Language and Literary Studies, 2023)
Utilizing mobile phone apps to enhance students’ English-speaking skills is not novel to teachers. Hallo is an app on which users make random audio calls with several callers from different countries in the world. Based on one feature of Hallo that for every 10-minute conversation with any speaker counts towards their consecutive use of the application over ten weeks. The case study was carried out to investigate the effectiveness of practicing English speaking on Hallo as daily at-home exercises. Ten English major sophomores at Hong Duc University were chosen to participate in the study lasting ten weeks. These students were required to make daily conversations about assigned topics on Hallo and then video-record them to send to the teacher for regular checking. The comparisons of pre-test and post-test results, interviews and classroom observations indicate that students made significant progress in English speaking skills and could communicate with others more fluently. The study suggests that the teacher should give detailed guidelines to help low-level students maximize the benefits of this app in mastering English speaking.